Barriers and Opportunities for MSME Development in Indonesia: Internal and External Perspectives - Ratnaningtyas, Heny; Wicaksono, Haryo; Irfal, Irfal (PT. Riset Press International, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in the Indonesian economy, contributing to GDP, creating jobs and reducing poverty. However, MSMEs in Indonesia face various challenges that hinder their development, such as limited managerial skills, lack of product innovation, and limited access to financing. This research aims to identify internal and external factors that influence the development of MSMEs in Indonesia and provide recommendations to support their growth. The approach used in this research is descriptive qualitative, with data collection methods through in-depth interviews, focus group discussions (FGD), and document studies in several large cities such as Jakarta, Bandung, Yogyakarta, and Surabaya. The research results show that the main internal factors hindering the development of MSMEs are a lack of managerial skills and product innovation. Meanwhile, external factors include limited access to financing and uneven government policies. Technology and digitalization provide excellent opportunities for MSMEs to increase their competitiveness, but limited digital skills remain an obstacle. In conclusion, managerial training, product innovation, and simplifying access to financing are necessary to encourage the growth of MSMEs. The government must also improve its socialization policy and ensure its implementation is evenly distributed throughout Indonesia.